Efficacy of some plant resistance inducers against several sunflower downy mildew (Plasmopara halstedii (Farl.) Berl. et de Toni) isolates - Yousif, Ahmed Ibrahim Alrashid; Almuslimawi, Alaa; Turóczi, György; Kiss, József; Kovács, Attila; Körösi, Katalin (Acta Biologica Szegediensis, 2023)
Plasmopara halstedii (Farl.) Berl. et de Toni is the oomycete that causes sunflower downy mildew (SDM). Traditional means of controlling this pathogen are using resistant hybrids, crop rotation and seed coating with fungicides. Disease control strategies that use a variety of approaches are becoming an increasingly essential aspect of pest management strategies. We conducted this exploratory investigation to evaluate whether specific plant resistance inducers might work against P. halstedii. In this study we used azadirachtin (AZA) a botanical insecticide; benzothiadiazole (BTH) and Trichoderma asperellum. Three-day-old susceptible sunflower seedlings were pre-treated with different doses of inducers for two hours. The seedlings were immediately inoculated of 7 different pathotype of P. halstedii. As a control, metalaxyl-M a systemic fungicide was used. Nine-day-old sunflower plant leaves were sprayed with bidistilled water to stimulate sporangial growth. In vivo experiments showed that BTH, T. asperellum and the highest doses of AZA significantly reduced downy mildew symptoms. The various pathotypes of the pathogen significantly affected the plant height and disease symptoms under experiments.